Transfer hospitalizations for pediatric severe sepsis or septic shock: resource use and outcomes - Folafoluwa O. Odetola; Achamyeleh Gebremariam (BMC, 2019)
Abstract Background Sepsis is a major cause of child mortality and morbidity. To enhance outcomes, children with severe sepsis or septic shock often require escalated care for organ support, sometimes necessitating interhospital transfer. The association between transfer admission for the care of pediatric severe sepsis or septic shock and in-hospital patient survival and resource use is poorly understood. Methods Retrospective study of children 0-20 years old hospitalized for severe sepsis or septic shock, using the 2012 Kids' Inpatient Database. After descriptive and bivariate analysis, multivariate regression methods assessed the independent relationship between transfer status and outcomes of in-hospital mortality, duration of hospitalization, and hospital charges, after adjustment for potential confounders including illness severity. Results Of an estimated 11,922 hospitalizations (with transfer information) for pediatric severe sepsis and septic shock nationally in 2012, 25% were transferred, most often to urban teaching hospitals. Compared to non-transferred children, transferred children were younger, and had a higher frequency of extreme illness severity (84% vs. 75%, p < .01), and of multiple organ dysfunction (32% vs. 24%, p < .01). They also had higher use of invasive medical devices including arterial catheters, invasive mechanical ventilation, and central venous catheters; and of specialized technology, including renal replacement therapy (6.2% vs. 4.6%, p < .01) and extracorporeal membrane oxygenation (5.7% vs. 1.8%, p < .01). Transferred children had longer hospitalization and accrued higher charges than non-transferred children (p < .01). Crude mortality was higher among transferred than non-transferred children (21.4% vs.15.0%, p < .01), a difference no longer statistically significant after multivariate adjustment for potential confounders (Odds Ratio:1.04, 95% Confidence interval: 0.88-1.24). Similarly, adjusted length of hospital stay and hospital charges were not statistically different by transfer status. Conclusion One in four children with severe sepsis or septic shock required interhospital transfer for specialized care associated with greater use of invasive medical devices and specialized technology. Despite higher crude mortality and resource consumption among transferred children, adjusted mortality and resource use did not differ by transfer status. Further research should identify quality-of-care factors at the receiving hospitals that influence clinical outcomes and resource use.